Penyucian Pendidikan Akuntansi Episode Dua: Hiper View of learning dan Implementasinya - Mulawarman, Aji Dedi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2008)
Accounting education needs desecularization of learning concept as well as its conventional accounting curriculum to suit main values of Indonesian society. Desecularization of accounting education must be conducted with the methodology of Purification based on love that is beyond all (hyperlove). The result is a synergy of reproductive view of learning and constructive view of learning and goes beyond both (hyperview of learning), also the use of various research methodologies according to specific need. The implementation of hyperview of learning is idea about general formulation about curriculum that possesses spiritual values, intuitwe-soul and material. Keywords: Hyperlove, hyperview of learning, research methodologies, curriculum